Pieni kuulijuus: taustamusiikki ja äänellinen kaupunkitila toisinkuulijoiden kokemana - Tarvainen, Anne; Kytö, Meri (Suomen musiikkitieteellinen seura, 2025)
This article examines the experiences of background music in urban spaces from the perspective of aural diversity. We study the experiences of individuals whose temporal or permanent auditory capacities, sensory experiences, or interpretations of soundscapes differ from prevailing socio-cultural norms of listening. Our approach draws on Marja-Liisa Honkasalo’s concept of small agency, which, in our study, highlights the small listening strategies individuals employ to navigate challenging sound environments. The data consists of sound diaries and interviews, analyzed through a transactional lens. The findings reveal that listeners’ agency is dynamic and situational, and that unmanaged elements of background music can either constrain their agency or foster creative responses. We argue that these aurally diverse experiences and their small listening strategies provide valuable insights into our listening cultures and challenge the auditory design of urban spaces to better accommodate aural diversity.